Feedback vertex set in alternating group graphs - Wang, Jian,; Gao, Xirong Xu Liqing,; Zhu, Dejun,; Yang, Yuansheng, (Utilitas Mathematica, 2017)
The feedback number of a graph G is the minimum number of vertices whose removal from G results in an acyclic subgraph. Use f(AGn) to denote the feedback number of the alternating group graphs AGn. This paper shows that. © 2015 Utilitas Mathematics.